Teaching Aids to Adults: A Resource for Acquired Immune Deficiency Syndrome Instruction - Appleby, George A.; Connecticut State Department of Education (State of Connecticut, Department of Education, 1989)
Keywords: AIDS (Disease); Study and teaching; dept.swk; faculty_collection

The Use of Mutual Aid by Russian-Jewish Immigrants in Two Connecticut Communities: An Analysis of an Informal Helping System - Siegel, Elbert (Thesis Ph.D.--Columbia University., 1988)
Keywords: Connecticut; History; History; Connecticut; Jews, Russian; dept.swk; faculty_collection

The Relationship of Program Change and Select Structural and Contextual Organizational Properties of Fifteen Mental Health Agencies - Appleby, George A. (Thesis D.S.W.--Columbia University., 1984)
Keywords: Administration; Mental health facilities; dept.swk; faculty_collection

Review of Dependency and Poverty: Old Problems in a New World, by June Axinn and Mark J. Stern - Baskind, Frank R. (Journal of social work education, 1989)
Keywords: dept.swk

Empowerment through collaboration in a state university system - Brower, Irene; Nancy Coleman; Ivry, Patricia; Leipzig, Barbara; Nemzer, Beatrice; Nilsson, Andrew; Sosnowitz, Barbara (Journal of Teaching in Social Work, 1989)
Historically, social workers have been aware of the power of group resources and the importance of networking for their clients and for themselves as professionals. This article is the outgrowth of a collaboration paper presented by the authors at the Association of Baccalaureate Social Work Program Directors Annual Conference on September 22, 1986 in San Antonio, Texas. Four separate social work education programs within a state university system formed an informal collaborative association to address common concerns, develop strategies to enhance resources and to foster mutual support. The context, developmental process, barriers, activities, issues, outcomes and benefits of the collaborative association are described. © 1989 Taylor & Francis Group, LLC.
Keywords: dept.swk

Social-work day to day - the experience of generalist social-work practice - wells,cc - Siegel, E (Journal of Social Work Education, 1989)
Keywords: dept.swk; ⛔ No DOI found

Book Review: Treating the elderly with psychotherapy - the scope for change in later life - sadavoy,j, leszcz,m - Saltz, CC (Social Casework-Journal of Contemporary Social Work, 1988)
Keywords: book.review; dept.swk

Suicide attempts and alcoholism - Hesselbrock, M.; Hesselbrock, V.; Syzmanski, K.; Weidenman, M. (Journal of Studies on Alcohol, 1988)
This study examined the association among suicide attempts, parental alcoholism, psychopathology and drinking history in a sample of hospitalized alcoholics. Suicide attempters were found to have multiple psychiatric diagnoses (e.g., depression, antisocial personality disorder and substance abuse) and more severe psychiatric symptoms than nonattempters. Alcoholic suicide attempters also tended to have a parental history of alcoholism and began abusing alcohol at an early age. Alcohol abuse symptoms during the month before, and 6 month before, the current hospitalization were generally similar for suicide attempters and nonattempters. Clinical implications of the findings are discussed.
Keywords: adult; age; alcoholism; dept.swk; epidemiology; female; human; male; mental disease; normal human; oral drug administration; preliminary communication; psychological aspect; suicide attempt

Book Review: AIDS and the law - a guide for the public - Dalton,HL, Burris,S - Appleby, George Alan (Social Casework-Journal of Contemporary Social Work, 1988)
Keywords: book.review; dept.swk

Impact of a geriatric consultation team on discharge placement and repeat hospitalization - Saltz, Constance C; Mcvey, Laura J; Becker, Peter M; Feussner, John R; Cohen, Harvey J (Gerontologist, 1988)
Keywords: age; consultation; dept.swk; hospitalization; human; major clinical study

Treatment outcome in depressed alcoholics - Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Alcoholism and Substance-Abuse - Course and Outcome - Hesselbrock, V; Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Effects of retesting with the beck and zung depression scales in alcoholics - Choquette, Keith A; Hesselbrock, Michie N (Alcohol and Alcoholism, 1987)
The present study assessed the presence of testing effects arising from the repeated administration of both the Beck and Zung depression scales to a group of 60 inpatient alcoholics. Thirty-seven men and 23 women were randomly assigned to one of three groups and administered the depression scales on one, two or three occasions, in successive weeks of treatment. Although the between group comparisons of initial test administration did not indicate a true change in depression, a within group comparison of initial with subsequent test administrations indicated a clear improvement in depression scores on both scales. Apparently the result of the reactive effects of testing, the within group differences could easily mislead a researcher into believing depression was alleviated when in fact it was not. This sizeable testing effect has obvious implications for studies which repeatedly assess depression. © 1987 Medical Council on Alcoholism.
Keywords: Adult; Aged; Aged, 80 and over; Alcoholism; Depressive Disorder; Emotions; Female; Hospitalization; Human; Male; Middle Age; Psychiatric Status Rating Scales; Support, U.S. Gov't, P.H.S.; Time Factors; adult; aged; alcoholism; article; clinical trial; depression; dept.swk; emotion; female; hospitalization; human; male; randomized controlled trial; rating scale; time; ⛔ No DOI found

Sources of strain between physicians and social workers: Implications for social workers in health care settings - Mizrahi, T.; Abramson, J. (Social Work in Health Care, 1985)
This paper analyzes the sources of strain between the professions of medicine and social work. The two professions are compared in relation to (1) the organization and socialization process of professional training; (2) perspectives on patient care, illness and role of the health care professional; (3) attitudes toward knowledge and data; (4) attitudes toward and preparation for teamwork; (5) perspectives on the role of the patient; (6) perceptions of social work’s function. © 1985 Taylor & Francis Group, LLC.
Keywords: Attitude of Health Personnel; Human; Internship and Residency; Interprofessional Relations; Medical Staff, Hospital; Patient Advocacy; Professional-Patient Relations; Role; Sick Role; Social Perception; Social Work; Socialization; dept.swk; human; organization and management; physician; psychological aspect; short survey; social aspect; social worker; training; united states

Parents' evaluations of genetic counselling. - Black, Rita Beck (Patient Counselling and Health Education, 1980)
Genetic counselling represents a new and important health service, but little is known about how the clients of genetic clinics actually experience and view the genetic counselling process. This paper reports on the evaluations made by clients of a genetics clinic and their recommendations for ways to improve and expand this service. In their comments, clients stressed the need for more time and individual attention from genetic counsellors, additional follow-up and supportive counselling, and increased efforts to educate the general public about birth defects. Their recommendations are discussed in terms of the implications for developing and improving genetic counselling services.
Keywords: anxiety; dept.swk; genetic counseling; heredity; medical education; medical examination; parent; prevention